Personal Hygiene and Knowledge as a Typhoid Fever Risk Factor in Muna City Hospital - Fitriani Fitriani; Mayusef Sukmana (Fakultas Kedokteran, 2020)
Data from WHO, the incidence thypoid fever in the world at 16- 33 millions with 500-600 thousand mortalities every year. Data from the Hospital District Muna year in 2013 amounted to 98 cases, while in 2014, the incidence of typhoid fever from january-april of 39 cases with 78 patients with fever. This study aims to determine the effect of knowledge and personal on the incidence of typhoid fever in hospitals Kab.Muna. This type of research is an analytic study with case-control design.. Number of samples in this study were as many as 78 people with the criteria of the sample is 39 cases and 39 controls were drawn from 78 population. The data were processed using univariate, bivariate, and odds ratio test. From the results of the study showed no significant effect between the knowledge of the value of OR = 2.671, the lower limit and upper limit = 0.830 = 8.603. With the value of personal hygiene OR = 2.170, the lower limit and upper limit = 0.786 = 5.993. Increased knowledge and awareness through counseling patients and healthy hygienic behavior is needed for prevention and control of typhoid fever occurrence in Muna District Hospital. Keywords: Knowledge , Personal Hygiene and typhoid fever.